Determinantes del sector exportador no tradicional del Departamento de Caldas y su comportamiento en el periodo 1980 a 2004 (2011)
Ésta investigación se centra en identificar los algunos factores que determinan las exportaciones no tradicionales (ENT) del Departamento de Caldas, como también el de presentar un análisis de la dinámica exportadora de Caldas durante el periodo 1980 – 2004. Para ello se utilizó un modelo econométrico en Datos de Panel, se utilizaron cifras del DANE, la DIAN, COMTRADE, UNSTAT, UNTAD, CEPAL, ILPES, DNP, Ministerio de Comercio, Industria y Turismo, entre otras. Como parte de los resultados se identificaron que los principales determinantes de las ENT del departamento son las variables de oferta, específicamente los salarios de la industria y el valor agregado, además la demanda externa tomada como el PIB de los socios comerciales, resultó muy relevante para explicar las ENT. Las variables relacionadas con los precios relativos, como índice de tasa de cambio real (ITCR) y volatilidad de la tasa de cambio real (VOLTCR), aunque tienen el signo esperado, no resultan significativas para explicar las ENT caldenses en el período estudiado./ Abstract: This research focuses on identifying factors that determine non-traditional exports (ENT) of Caldas Department, as well as to present an analysis of the dynamics of Caldas exports in the period 1980 to 2004. We used an econometric panel data with information of DANE, DIAN, COMTRADE, UNSTAT, UNTAD, CEPAL, ILPES, DNP, Ministry of Commerce, Industry and Tourism, among others. As part of the results, we identified that the main determinants of the ENT Department are supply variables, namely manufacturing wages and industrial value added and GDP of trading partners as foreign demand indicator, it was very relevant to explain ENT. Variables related to relative prices, as an index of real exchange rate (ITCR) and volatility of real exchange rate (VOLTCR), although the expected sign, are not significant to explain the ENT Caldas in the period studied. As part of the results, there were identified that the principal determinants of the ENT of Department are the variables of offer, specifically the wages of the industry and the value added, in addition the external demand taken as the GDP of the commercial partners, it turned out to be very relevant to explain the ENT. The variables related to the relative prices, as index of real exchange rate (ITCR) and their volatility (VOLTCR), though they have the expected sign, do not turn out to be significant to explain the ENT of Caldas in the studied period.